The effectiveness of dyadic interventions for health outcomes of prostate cancer patients and informal caregivers: a systematic review and meta-analysis - Yuan Xiao; Jiao Sun; Min Liu; Haifeng Wang; Jingjing Guan (BMC Nursing)
Abstract Background Prostate cancer is a worldwide health issue, and current prostate cancer care extends to the patient‒caregiver dyadic setting, where individuals are interdependent and interact with each other as well as possible negative psychological and behavioural outcomes. However, the impact of dyadic care interventions on health outcome indicators for prostate cancer patients and their informal caregivers has yet to be examined. Aim To describe the characteristics of dyadic interventions involving patients with prostate cancer and their informal caregivers and investigate their effects on psychosocial health, sexual health, and dyadic relationships. Methods Ten electronic databases (Web of Science, Cochrane Library, PsycINFO, PubMed, Embase, CINAHL, CNKI, Wanfang, VIP, and SinoMed) were thoroughly searched for related publications published between the database’s founding and April 2024. The risk of bias for the included studies was evaluated using the Cochrane risk-of-bias tool, and a meta-analysis was performed using RevMan 5.4. Results This study identified and evaluated 19 RCTs reporting 22 different interventions, as well as outcome indicators for the three aspects of psychosocial health, sexual health, and dyadic relationships in prostate cancer patients and informal caregivers. A meta-analysis of pooled data revealed that for prostate cancer patients, the intervention improved dyadic coping (SMD95% CI [95% CI] = 0.22 [0.01;0.42], p = 0.04), and for informal caregivers the dyadic care intervention reduced anxiety (SMD95% CI [95% CI] = -0.35 [-0.65;-0.06], p = 0.02), enhanced self-efficacy (SMD [95% CI] = 0.22 [0.01;0.43], p = 0.04), and improved sexual functioning (SMD [95% CI] = 0.29 [0.05;0.54], p = 0.02). No statistically significant overall effects were observed for the other outcome indicators. Conclusion The results of this review indicate that dyadic care interventions benefit prostate cancer patients and informal caregivers. However, given features such as research quality and sample size, further randomized controlled trials with excellent study designs are needed in the future to evaluate and validate the efficacy of dyadic care treatments for patients with prostate cancer. Trial registration The protocol for this study is registered in PROSPERO with registration number (CRD42024567542).